Disrupt Medicine - Mihai Nadin (Journal of Biology and Medicine - Peertechz Publications, 2021)
Current medicine is anchored in reactive practice. Modern medicine became an extension of the physics and chemistry based on the Cartesian reductionist-deterministic view of the world. However, reaction is more expensive, by many orders of magnitude, than anticipatory actions; and in the long run, it is unsustainable. If physicians do not want to be replaced by machines-neither by 2035 (as medical experts already predicted) nor ever-they should stop treating human beings as machines. Only anticipation-grounded medicine can save medicine from itself.